Nanoparticle-Mediated Targeting of the Arthritic Joint: A Critical Narrative Review of Drug Delivery and Molecular Therapy - Jharna Sahu; Chandrika Ahirwal (Journal of International Research in Medical and Pharmaceutical Sciences, 2026)
Nanoparticle-based delivery is being developed to concentrate anti-inflammatory, disease-modifying and molecular therapeutics within arthritic joints while limiting systemic exposure. Yet “joint targeting” encompasses several distinct problems: vascular access to inflamed synovium, persistence after intra-articular administration, penetration through dense avascular cartilage, cell-selective uptake and release of an active payload at the intended intracellular or extracellular site. This critical narrative review evaluates how these constraints differ between rheumatoid arthritis (RA) and osteoarthritis (OA), and how they shape the performance of lipid, polymeric, inorganic and biomimetic nanocarriers. Literature published from 1 January 2000 to 19 June 2026 was considered, with emphasis on verified peer-reviewed original studies, recent reviews and clinically informative evidence. In RA, long-circulating carriers can exploit inflammation-associated vascular permeability, while folate receptor, CD44 and endothelial ligands can add cellular or tissue selectivity. In OA, direct intra-articular administration bypasses systemic access but creates a more demanding transport problem because rapid joint clearance and the highly charged extracellular matrix of cartilage limit durable chondrocyte exposure. Peptide affinity and reversible electrostatic interactions offer particularly strong mechanistic rationales for cartilage penetration and retention. Small interfering RNA, messenger RNA, cytokines, glucocorticoids and regenerative proteins broaden the therapeutic repertoire, but their success depends on cytosolic delivery, release kinetics and target engagement rather than localisation alone. Human evidence remains sparse. A randomised trial of pegylated liposomal prednisolone in RA provides the clearest clinical signal, whereas most OA systems remain at explant, rodent or rabbit stages. Across both diseases, fluorescence persistence, short-term histology and reductions in inflammatory markers often overstate translational maturity. Progress will require cell-resolved pharmacokinetics, disease-relevant models, intact-carrier measurements, rigorous comparators, long-term safety assessment and manufacturable formulations linked to clinically meaningful endpoints.